In situ nuclear DNA methylation in dilated cardiomyopathy: an endomyocardial biopsy study. (23rd January 2020) - Watanabe, Takatomo; Okada, Hideshi; Kanamori, Hiromitsu; Miyazaki, Nagisa; Tsujimoto, Akiko; Takada, Chihiro; Suzuki, Kodai; Naruse, Genki; Yoshida, Akihiro; Nawa, Takahide; Tanaka, Toshiki; Kawasaki, Masanori; et al.
Abstract: Aims: Although distinct DNA methylation patterns have been reported, its localization and roles remain to be defined in heart failure. We investigated the cellular and subcellular localization of DNA methylation and its pathophysiological significance in human failing hearts. Methods and results: Using left ventricular (LV) endomyocardial biopsy specimens from 75 patients with dilated cardiomyopathy (DCM; age: 58 ± 14 years old, %female: 32%) and 20 patients without heart failure (controls; age: 56 ± 17 years old, %female: 45%), we performed immunohistochemistry and immunoelectron microscopy for methylated DNA, 5‐methylcytosine (5‐mC). We next investigated possible relations of the incidence of 5‐mC‐positive (%5‐mC + ) cardiomyocytes with clinicopathological parameters. Immunopositivity for 5‐mC was detected in the cardiomyocytes and other cell types. The %5‐mC + cardiomyocytes was significantly greater in DCM hearts than in controls (57 ± 13% in DCM vs. 25 ± 12% in controls, P < 0.0001). The localization of 5‐mC immunopositivity in cardiomyocyte nuclei coincided well with that of heterochromatin, as confirmed by immunoelectron microscopy. Substantial DNA methylation was also observed in interstitial non‐cardiomyocytes, but the incidences did not differ between control and DCM hearts (39 ± 7.9% in DCM vs. 41 ± 10% in controls, P = 0.4099). In DCM patients, the %5‐mC + cardiomyocytes showed a significant inverse correlation with LV functional parameters such as heart rate ( r = 0.2391, P = 0.0388), end‐diastolic pressure ( r = 0.2397, P = 0.0397), and ejection fraction ( r = −0.2917, P = 0.0111) and a positive correlation with LV dilatation (volume index at diastole; r = 0.2442, P = 0.0347; and volume index at systole; r = 0.3136, P = 0.0062) and LV hypertrophy (mass index; r = 0.2287, P = 0.0484)—that is, LV remodelling parameters. No significant correlations between DNA methylation and the histological parameters of the biopsies, including cardiomyocyte hypertrophy, fibrosis, and inflammatory cell infiltration, were noted. Conclusions: The present study revealed increased nuclear DNA methylation in cardiomyocytes, but not other cell types, from DCM hearts, with predominant localization in the heterochromatin. Its significant relations with LV functional and remodelling parameters imply a pathophysiological significance of DNA methylation in heart failure.